Winter as an artistic image in Rauf Parfi's poetry (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
Rauf Parfi is a creative artist. His lyrics have won the love of readers with their originality and uniqueness. Especially the poems dedicated to the description of nature leave a special impression on poets. Famous theoretician Bahadir Sarimsakov writes: "If life is poetry for a real poet, then poetry is his life. I observed this in the life and work of many poets and poetesses, and I admitted that qualities such as innate intelligence, strong emotions, strong character and justice must be embodied in the poet's personality. If one of these qualities is lacking, the product of the poet's work will be defective.